Sport as Therapy - Martins W (Dynamic Media Sales Verlag, 2021)
Introduction: Few studies are available on the acute effects of motor racing on race drivers lactacidemia and blood glucose. Objective: To verify changes in lactacidemia and glycemia of race car drivers in the Old Stock Race category. Method: The concentrations of plasma lactate and glycemia of eight male race car drivers in the Old Stock Race category (OSR) were recorded thirty minutes before the start and ten minutes after the start of the race. The data were obtained during the 4th round of the 2018 Season of the OSR held at the Jos Carlos Pace race track (Interlagos / So Paulo-Brazil). For comparison between moments, paired Students t-test paired on variables with normal distribution was used, with Bonferronis post-test, adopting a 5% significance level, for all analyses. Descriptively the data were compared using the Percentage Delta and presented in graphical and tabular form.Results: It was found that the lactate concentration increased significantly after the race (2.26 + 0.76 vs. 3.56 + 0.97 mmol / L, p = 0.0101). On the other hand, there was no change in blood glucose (122 +15.3 vs. 123 + 19.8 mg / dl, p = 0.8828).Conclusion: The significant increase in lactacidemia after the race indicates that there was an anaerobic muscle requirement during the race. On the other hand, there was no change in the mean blood glucose after the race.Key Words:Motor Racing, Human Performance, Exercise, Experimental Research